Comparing Efficacy and Side Effects of Memantine vs. Risperidone in the Treatment of Autistic Disorder - Nikvarz, Nikvarz; Alaghband-Rad, Javad; Tehrani-Doost, Mehdi; Alimadadi, Abbas; Ghaeli, Padideh (Pharmacopsychiatry, 2017)
Introduction: This study was aimed to compare the efficacy and side effects of memantine, an antagonist of the NMDA receptor of glutamate, with risperidone given the fact that glutamate has been noted for its possible effects in the pathogenesis of autism. Risperidone, an atypical antipsychotic, has been approved by FDA for the management of irritability associated with autism.Methods: 30 children, aged 4–17 years, entered an 8-week, randomized trial. Patients were randomly assigned to receive either risperidone or memantine. Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), Clinical Global Impressions – Improvement (CGI-I) and Clinical Global Impression-Severity (CGI-S) scales were used to assess behavioral symptoms of the patients.Results: Both risperidone and memantine reduced the scores of 4 subscales of ABC as well as the 10-item and the total score of CARS significantly. However, differences between the 2 drugs in the scores of each evaluating scale were not found to be significant. Relatively, larger number of patients on risperidone showed “very much improvement” when assessed by CGI-I scale when compared with those on memantine.Discussion and conclusion: The present study suggests that memantine may have beneficial effects in the treatment of many core symptoms of autism. Therefore, memantine may be considered as a potential medication in the treatment of those autistic children who do not respond or cannot tolerate side effects of risperidone.
Keywords: autistic disorders; risperidone; memanine